DESIGN AND IMPLEMENTATION OF DANCESPORT VIDEO TEACHING SYSTEM BASED ON MODEL-VIEW-CONTROLLER (MVC) - Yuanxin, Lyu; Saearani, Muhammad Fazli Taib (Greget: Jurnal Kreativitas dan Studi Tari, 2025)
Dancesport, a form of social dance that blends competition with artistry, serves as both a cultural enrichment activity and a fitness choice for many. Despite its benefits, traditional Dancesport instruction typically requires in-person classes, which can limit accessibility due to constraints of time and location. As a result, many enthusiasts miss out on fully experiencing the joy of dance. However, advancements in computer networks and communication technology have paved the way for online teaching to become a practical alternative. Addressing the specific needs of modern Dancesport education, this paper focuses on the development of a video teaching system using MVC architecture. By integrating technologies such as Freemarker templates, Hibernate frameworks, the MySQL 5.0 database, and Hadoop, the system is designed to enhance Dancesport learning. The project includes a comprehensive analysis of the functional requirements for the system, followed by an overall design plan. Key functional modules are thoroughly examined to ensure the system meets the unique demands of Dancesport instruction, providing an innovative solution for accessible and engaging dance education.